Spatial and Temporal Variability of Rainfall in the Western Region of Nepal - Gaire, Amrit; Bagale, Damodar; Acharya, Prabin; Acharya, Ram Hari (Journal of Hydrology and Meteorology, 2024)
The temporal and spatial variability of seasonal, annual, and decadal rainfall over 44 years in western Nepal was investigated using rainfall data from 36 meteorological stations in various physiographic regions. Missing data were addressed using the normal ratio method, and significant trends in annual rainfall were assessed through the Man-Kendall test. Western Nepal receives about 79.7% of annual rainfall during the monsoon, followed by 10.7% during the pre-monsoon, 3.3% during the post-monsoon, and 6.3% during the winter. The analysis revealed distinct seasonal excess and deficit episodes, with the highest monsoon rainfall recorded in 2000 and the lowest in 1979. During the study period, there is a large temporal variability of seasonal and annual rainfall. The central part of western Nepal receives heavy rainfall in monsoon seasons than other parts. In winter seasons more rainfall is received in the Northwest part and decreases towards the central and eastern parts of western Nepal. The midlands of western Nepal received higher annual rainfall than the other regions. The present study identified that the seasonal rainfall has been decreasing patterns in the Western region of Nepal for the past four decades.